2009
DOI: 10.1002/pmh.69
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of women who continue and discontinue treatment for borderline personality disorder

Abstract: Background Treatment non-completion is a signifi cant problem for personality disorder treatment services. Aims We investigated differences between treatment continuers and treatment discontinuers of a tertiary specialist service for people with borderline personality disorder. The two groups were compared on: (1) personality disorder severity; (2) motivation for therapy; (3) mood; and (4) social problem solving. Method Patients' personality disorders were examined using the International Personality Disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…The high dropout rate we found in an early phase of BPD is widely supported by previous studies and probably depends on dysfunctional personality traits of these patients that mainly affect interpersonal relationships 3–8 . The present research confirms these data and shows that dropout is strongly associated with patients' subjective perception, which is assessed through PAEQ and includes: therapeutic relationship, patients' expectations regarding the effectiveness of the treatment, and their motivation for change.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high dropout rate we found in an early phase of BPD is widely supported by previous studies and probably depends on dysfunctional personality traits of these patients that mainly affect interpersonal relationships 3–8 . The present research confirms these data and shows that dropout is strongly associated with patients' subjective perception, which is assessed through PAEQ and includes: therapeutic relationship, patients' expectations regarding the effectiveness of the treatment, and their motivation for change.…”
Section: Discussionsupporting
confidence: 89%
“…S ATISFACTORY THERAPEUTIC COMPLIANCE among patients with personality disorder (PD) is challenging and notoriously difficult to achieve in all treatment settings and especially when a borderline personality disorder (BPD) diagnosis is present. [1][2][3] In particular, dropout, ranging from 50% to 60%, mainly occurs in the early phase of treatment. [4][5][6] Despite the importance of this problem, very little research on predictors of premature termination of treatment for BPD has been carried out.…”
mentioning
confidence: 99%
“…), and that non‐completion is associated with poorer clinical outcomes (Karterud et al . , Webb & McMurran ) and increased service costs (Sampson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews have shown that one third of people with PD do not complete treatment (McMurran et al 2010), and that non-completion is associated with poorer clinical outcomes (Karterud et al 2003, Webb & McMurran 2009) and increased service costs (Sampson et al 2013). This information was the catalyst for developing this training programme to improve engagement and prevent noncompletion.…”
Section: Discussionmentioning
confidence: 99%
“…This review also identified studies that showed non-completion of treatment to be associated with poorer clinical outcomes. Compared with treatment completers, those who did not complete treatment were shown to be hospitalized more frequently and to spend more days in hospital [4,5]. Poor attendance also compromises service efficiency and cost-effectiveness through poor use of resources and consequent increased costs associated with treatments [1].…”
Section: Introductionmentioning
confidence: 99%